1998
DOI: 10.1093/emboj/17.21.6241
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of phospholipase C-β2by the Rho GTPases Cdc42Hs and Rac1

Abstract: Neutrophils contain a soluble guanine-nucleotidebinding protein, made up of two components with molecular masses of 23 and 26 kDa, that mediates stimulation of phospholipase C-beta2 (PLCbeta2). We have identified the two components of the stimulatory heterodimer by amino acid sequencing as a Rho GTPase and the Rho guanine nucleotide dissociation inhibitor LyGDI. Using recombinant Rho GTPases and LyGDI, we demonstrate that PLCbeta2 is stimulated by guanosine 5'-O-(3-thiotriphosphate) (GTP[S])-activated Cdc42Hsx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 49 publications
(81 reference statements)
6
91
0
Order By: Relevance
“…Evidence for a tight connection between PLC␤ 2 and Rho GTPases in cells is provided by the chemoattractant receptor system, whose activation stimulates PLC␤ 2 and Rac1, Rac2 and Cdc42 (8 -11). Moreover, in accord with our in vitro studies on PLC␤ 2 activation by Rho GTPases (4,6), a recent study conducted on myeloid-differentiated HL-60 cells demonstrated that dominant-negative Cdc42 disrupted the stimulation of inositol 1,4,5-trisphosphate formation mediated via the chemoattractant receptors while inhibiting Rac2 activation (12). These findings strongly support the notion that Rac2 and possibly Rac1 and Cdc42 are critically involved in receptormediated stimulation of PLC␤ 2 activity.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Evidence for a tight connection between PLC␤ 2 and Rho GTPases in cells is provided by the chemoattractant receptor system, whose activation stimulates PLC␤ 2 and Rac1, Rac2 and Cdc42 (8 -11). Moreover, in accord with our in vitro studies on PLC␤ 2 activation by Rho GTPases (4,6), a recent study conducted on myeloid-differentiated HL-60 cells demonstrated that dominant-negative Cdc42 disrupted the stimulation of inositol 1,4,5-trisphosphate formation mediated via the chemoattractant receptors while inhibiting Rac2 activation (12). These findings strongly support the notion that Rac2 and possibly Rac1 and Cdc42 are critically involved in receptormediated stimulation of PLC␤ 2 activity.…”
supporting
confidence: 88%
“…as the mutant PLC␤ 2 ⌬ that lacks the Phe 819 -Glu 1166 segment, are resistant to stimulation by ␣ q but are susceptible to activation by Rho GTPases and G protein ␤␥ subunits (3,4,7). Recent studies (4 -6) show that ␤␥ dimers and Rho GTPases activate PLC␤ 2 by interacting with different regions of the effector enzyme.…”
mentioning
confidence: 99%
“…After 20 h, the cells were serum-starved for another 24 h, homogenized, and fractionated into postnuclear particulate (P) and soluble (S) fractions as described under "Experimental Procedures." The two fractions were well separated, as controlled by immunoblotting for RhoGDI␣ (cytosolic) and G␤ [1][2][3][4][5] (membrane-bound, not shown). Equal proportions (v/v) of the P and S fractions of each sample were subjected to SDS-PAGE and quantified by immunoblotting and densitometry using anti-GFP antibodies.…”
Section: Plc␤ 2 Activation By Different Stimulators Can Occur Atmentioning
confidence: 99%
“…Rac1, 2, 3, and to a lesser extent Cdc42Hs, were shown to activate PLC-β2 and β3 [60,61] by binding to their PH domains [11,61]. This binding was thought to activate the PLC-βs by recruiting them to the membrane surface [62].…”
Section: Protein Activators Of Plc-βsmentioning
confidence: 99%